Metternich's League to Preserve Peace and the Conservative Elites' Doubts about the Functionality of the Post-Napoleonic Order - Šedivý, Miroslav (Cambridge University Press, 2024)
Before 1848 not merely democrats and liberals criticized the post-Napoleonic order for their growing mistrust of its ability to protect the sovereignty of smaller countries and preserve the general peace. The predominantly conservative ruling elite, namely rulers, statesmen, and diplomats, raised the same criticism when the law-breaking and abuse of power made them similarly mistrustful of the state of European politics during the 1830s and 1840s. This became true even for some of the order's authors like Austrian chancellor Metternich who serves as a prominent example of this mistrust with his project of a league to preserve peace in Europe in August 1840. Metternich, who helped to create this order in 1815, found it defective and in need of improvement only a quarter of a century later. He certainly did not want to create a completely new international order and law of nations as some liberals and democrats desired at that time, but his idea was still, in a certain sense, revolutionary since its realization would have fundamentally modified the pillars on which the order had been founded at the end of the Napoleonic Wars.
Metternichova liga k zachování míru a pochyby konzervativních elit o funkčnosti postnapoleonského pořádku
Keywords: Metternich; peace; Europe; 1840; Rhine Crisis; post-Napoleonic order; Metternich; mír; Evropa; 1840; Rýnská krize; postnapoleonský pořádek